The immune landscape and viral shedding of Omicron SARS-CoV-2 variants implicate immune escape - Zhang, Weilong; Gai, Xiaoyan; Duan, Zhonghui; Yan, Changjian; Huang, Chunyuan; Wu, Chaoling; Zheng, Siping; Lin, Zixiang; Zhou, Qingtao; Dai, Lili; Yang, Ping; Bao, Fang; et al. (Frontiers in Medicine, 2025)
BackgroundThree years into the SARS-CoV-2 pandemic, the virus continues to mutate despite widespread vaccination, posing ongoing challenges for epidemic prevention and control. The relationship between viral shedding and immune escape remains under investigation. This study aims to examine the association between viral shedding and immune escape in the BA.4/5 and BF.7 variants.MethodWe included 542 patients infected with the Omicron variant from Beijing Xiaotangshan shelter hospital. Based on the viral strain, patients were divided into BA.4/5 group and BF.7 group. Additionally, we categorized patients into rapid viral shedding and slow viral shedding groups according to their viral shedding rates. We explored the relationship between viral shedding and immune-related clinical indicators during this period.ResultOf the 542 patients, 118 were infected with BA.4/5 variant, and 424 were infected with BF.7 variant. The viral shedding duration differed significantly between BA.4/5 and BF.7 groups (p < 0.0001). However, there was no statistically significant correlation between viral shedding duration and immune-related indicators, such as WBC, Hb, PLT, Neu, Lym, CRP, allergy, fever, and vaccination status (p > 0.05). Furthermore, viral shedding duration was not associated with vaccination status, intervals between vaccinations, or vaccine types (p > 0.05).ConclusionThe duration of viral shedding in patients infected with Omicron variants BA.4/5 and BF.7 is not associated with WBC, Hb, Lym, CRP, fever, allergy, or vaccine-related indicators. This lack of association may be attributed to immune escape mechanisms.